2006
DOI: 10.1161/circulationaha.105.586198
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Guidelines Improves the Standard of Care

Abstract: Background-The purpose of this study was to determine whether implementation of recent guidelines improves in-hospital mortality from acute ST-elevation myocardial infarction (STEMI) in a metropolitan area. Methods and Results-We organized a network that consisted of the Viennese Ambulance Systems, which is responsible for diagnosis and triage of patients with acute STEMI, and 5 high-volume interventional cardiology departments to expand the performance of primary percutaneous catheter intervention (PPCI) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
62
1
11

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(86 citation statements)
references
References 25 publications
7
62
1
11
Order By: Relevance
“…The results of the CAPTIM (Comparison of Primary Angioplasty and Pre‐hospital Fibrinolysis in Acute Myocardial Infarction) study indicated that prehospital fibrinolysis, particularly in the first 2 hours after symptoms onset, can be more effective than transfer for primary PCI 20. In fact, 2 major registries—the Vienna STEMI Registry21 and the French Registry on Acute ST‐Elevation and Non‐ST‐elevation Myocardial Infarction (FAST‐MI) 201022—showed similar results for patients treated at an early stage.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the CAPTIM (Comparison of Primary Angioplasty and Pre‐hospital Fibrinolysis in Acute Myocardial Infarction) study indicated that prehospital fibrinolysis, particularly in the first 2 hours after symptoms onset, can be more effective than transfer for primary PCI 20. In fact, 2 major registries—the Vienna STEMI Registry21 and the French Registry on Acute ST‐Elevation and Non‐ST‐elevation Myocardial Infarction (FAST‐MI) 201022—showed similar results for patients treated at an early stage.…”
Section: Discussionmentioning
confidence: 99%
“…(2013) in Denmark, Kalla et al. (2006) in Austria, Danchin et al. (2008) in France, and Le May et al.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, several strategies have been developed to minimize the delay. In addition to inhospital and outpatient frameworks, educational programmes for timely medical care-seeking behaviour and prehospital protocols have been designed to improve outcomes [13][14][15][16]. Although the cause of prehospital delay in ACS is multifactorial and the duration from onset of symptoms until care-seeking is in part dependent on nonadjustable (patient) characteristics [17], some factors that cause delay in reperfusion after medical care-seeking are modifiable.…”
Section: Early Diagnosismentioning
confidence: 99%